2016
DOI: 10.1002/jmri.25420
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the airway in infants with MRI using pointwise encoding time reduction with radial acquisition (PETRA)

Abstract: 3 J. Magn. Reson. Imaging 2017;45:839-844.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Recently, Ohno et al demonstrated improved pulmonary nodule detection rates of thin-section MRI with UTE and further described the usefulness of UTE for evaluation of nodule type as at least as efficacious as standard-dose thin-section CT. 33 Other studies using UTE-sequences have shown a good visualization of the lung parenchyma and mediastinum in adult patients 34,35 as well as a good visibility of the airways including the trachea and main bronchi in infants. 36 There are several limitations that have to be considered in the present study. There are only a limited number of patients included in this study which is why our results must be regarded as initial results with the introduced sequences and any conclusions drawn from the present analysis awaits further proof in bigger (ideally multicentric) observations.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Ohno et al demonstrated improved pulmonary nodule detection rates of thin-section MRI with UTE and further described the usefulness of UTE for evaluation of nodule type as at least as efficacious as standard-dose thin-section CT. 33 Other studies using UTE-sequences have shown a good visualization of the lung parenchyma and mediastinum in adult patients 34,35 as well as a good visibility of the airways including the trachea and main bronchi in infants. 36 There are several limitations that have to be considered in the present study. There are only a limited number of patients included in this study which is why our results must be regarded as initial results with the introduced sequences and any conclusions drawn from the present analysis awaits further proof in bigger (ideally multicentric) observations.…”
Section: Discussionmentioning
confidence: 98%
“…UTE achieved a higher parenchymal signal and fewer motion artifacts compared to a 3 D fast gradient recalled echo sequence in ten free-breathing non-sedated infants. The visibility of central airways in 37 infants (23 -43 gestational weeks) at 3 T using PETRA was good in 90 % of the main airways, but only 22 % for the right upper lobe bronchus [39].…”
Section: Neonatal Lung Diseasementioning
confidence: 90%
“…Indeed, 3D-USV was not silent, whereas the quiet PETRA sequence might improve acceptability of the MR examination, especially in the pediatric population. 15,29 Finally, evaluation in human diseases was performed in a few adult patients only and requires evaluation in larger multicenter cohorts from childhood to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not explore whether this result might be related to hardware capacities or clinical tolerability of volunteers to long acquisition times. Indeed, 3D‐USV was not silent, whereas the quiet PETRA sequence might improve acceptability of the MR examination, especially in the pediatric population . Finally, evaluation in human diseases was performed in a few adult patients only and requires evaluation in larger multicenter cohorts from childhood to adulthood.…”
Section: Discussionmentioning
confidence: 99%